Antibiotic use attributable to RSV infections during infancy—an international prospective birth cohort study - Hak, Sarah F.; Venekamp, Roderick P.; Billard, Marie-Noëlle; Cianci, Daniela; Van Houten, Marlies A.; Pollard, Andrew J.; Heikkinen, Terho; Cunningham, Steve; Millar, Margaret; Martinon-Torres, Federico; Dacosta-Urbieta, Ana; Bont, Louis J.; et al. (OXFORD UNIV PRESS, 2025)
Background Early-life antibiotic use impacts microbiome composition and contributes to the emergence of antimicrobial resistance. Despite respiratory syncytial virus (RSV) being a leading cause of acute respiratory infections (ARI), accurate estimates of antibiotic use attributable to RSV are lacking.
Objectives To assess RSV-associated antibiotic use during the first year of life.
Patients and methods The RESCEU birth cohort study followed healthy term infants, born (n = 9154) between 1 July 2017 and 31 July 2020 from five European countries, to identify RSV-ARI hospitalizations during infancy. In a nested cohort (n = 993), we performed active RSV surveillance by collecting nasal swabs in case of ARI symptoms during RSV seasons (October-April). Antibiotic use during hospitalization was identified through chart review, while outpatient data were collected via parental questionnaires.
Results In the total cohort, antibiotics were used in 22.8% of RSV hospitalizations (33/145) and 62.5% of RSV intensive care admissions (5/8). In the nested cohort, antibiotics were used in 5.2% of any-severity RSV-ARI (13/250) and 9.9% of medically attended RSV-ARI (13/131). This results in an estimated incidence of 1.3% (95%CI: 0.8-2.0) of healthy term infants receiving >= 1 course of antibiotics associated with RSV infection in their first year, with an incidence rate of 1.1 RSV-associated antibiotic prescriptions per 1000 infant-months (95%CI: 0.6-1.9). As such, RSV accounts for 22.9% of antibiotic prescriptions for ARI during RSV seasons.
Conclusions One in 77 healthy term infants receives antibiotics during RSV infection before their first birthday. Real-world evidence is needed to establish the impact of RSV immunization on antibiotic use during infancy.
Clinical Trials Registration NCT03627572.